Efficacy and suitability of adding short-term psychodynamic psychotherapy (STPP) to pharmacotherapy in patients with depressive disorders: a systematic review - Gabriele Di Salvo; Camilla Perotti; Valerio Ricci; Giuseppe Maina; Gianluca Rosso (Trends in Psychiatry and Psychotherapy)
Abstract Objective: Recent guidelines on depressive disorders suggest a combination of antidepressants and psychotherapy in case of moderate to severe symptomatology. While cognitive behavioral therapy (CBT) and interpersonal therapy (ITP) are the most investigated interventions, psychodynamic psychotherapies have been less explored. The aim of this paper is to systematically review literature data on the efficacy of short-term psychodynamic psychotherapy (STPP) in combination with antidepressants in the treatment of depressive disorders, focusing on both short and long-term results and on potential moderators that could influence its effectiveness. Methods: This systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Databases searched were PubMed, Ovid, Scopus, and Cochrane Library, from inception to August 2023. Results: Adding STPP to medications in the first 6 months of treatment did not influence remission rates, but did improve acceptability, work adjustment, interpersonal relationships, social role functioning, hospitalization rates, and cost-effectiveness. After 12 months, a significant difference in remission rates arose, favoring combined therapy. From a long-term perspective, adding STPP to pharmacotherapy reduced the recurrence rate by almost 50%. STPP has proven to be more effective in longer depressive episodes, in more severe depression, and in patients with a history of childhood abuse. However, STPP had no impact on major depressive disorder (MDD) with comorbid obsessive-compulsive disorder (OCD). Conclusions: Combining STPP with antidepressants appeared to be helpful from both short-term and long-term perspectives. Still, there are few rigorous studies with large samples and further research is needed to identify which subgroups of patients may benefit more from STPP.